The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/cercor/bhj023
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Excitatory Receptive Fields of Infragranular Forelimb Neurons in the Rat Primary Somatosensory Cortex Responding To Touch

Abstract: We quantitatively studied the excitatory receptive fields of 297 neurons recorded from the forelimb infragranular somatosensory cortex of the rat while touch stimuli were applied to discrete locations on the forelimbs. Receptive fields were highly heterogeneous, but they were regulated, on average, by an underlying spatio-temporal structure. We found the following. (i) Neurons responded with decreasing magnitude and increasing latency when the stimulus was moved from the primary location to secondary locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 102 publications
10
29
0
Order By: Relevance
“…Yet, we also found evidence consistent with cortical sources of inhibition (Davis et al 2003;Fitzpatrick et al 1999;Hubel and Wiesel 1965;Nelken and Young 1994;Shofner and Young 1985;Spirou and Young 1991;Walker et al 1999;Webb et al 2005;Wehr and Zador 2003). Thus our findings indirectly support recent views that suppressive response components arise from a combination of cortical and subcortical sources rather than from the traditional model of suppression from cortical sources only [e.g., Sachdev et al (2012) review].…”
Section: Possible Significance Of Widespread Suppressive Response Comsupporting
confidence: 89%
See 2 more Smart Citations
“…Yet, we also found evidence consistent with cortical sources of inhibition (Davis et al 2003;Fitzpatrick et al 1999;Hubel and Wiesel 1965;Nelken and Young 1994;Shofner and Young 1985;Spirou and Young 1991;Walker et al 1999;Webb et al 2005;Wehr and Zador 2003). Thus our findings indirectly support recent views that suppressive response components arise from a combination of cortical and subcortical sources rather than from the traditional model of suppression from cortical sources only [e.g., Sachdev et al (2012) review].…”
Section: Possible Significance Of Widespread Suppressive Response Comsupporting
confidence: 89%
“…Yet, similar to results for excitatory RFs, we revealed effects of single-site stimulation that occurred far from each neuron's excitatory mRF across distant digits or palm pads. As reported by Tutunculer et al (2006), we also found evidence to suggest that the response types to tactile stimuli were more closely related to cortical separations within the hand representation than to separations between contiguous surfaces of the physical hand. Furthermore, neuronal activity recorded from a selected cortical electrode in response to stimulation of sites across the hand suggested that lateral interactions involving firing suppression occur not only along the representation of a single digit (in the rostral-caudal dimension in cortex) but also between digits (across the medial-lateral dimension in cortex).…”
Section: Properties and Extent Of Widespread Responses And Suppressivsupporting
confidence: 86%
See 1 more Smart Citation
“…Although our experimental anesthetized conditions represent a good model of passive unexpected stimuli during quiet behaviors (Krupa et al, 2004;Ferezou et al, 2006), it is important to remark that inferences about how stimuli are processed by behaving animals based on anesthetized data should be cautious. Nevertheless, the loss of spatial selectivity resulting from the large receptive fields-not only in the thalamus but also in the cortex (Ghazanfar and Nicolelis, 1999;Tutunculer et al, 2006;Moxon et al, 2008)-could be the price paid by sensory systems to fully benefit from the high information capacity of spike timing codes .…”
Section: Spike Timing Information In the Ventrobasal Complex Of The Tmentioning
confidence: 99%
“…Recent studies in the Moxon laboratory examined how sensorimotor information is encoded in normal animals and how this encoding is affected by spinal cord injury. Before hemisection, cells within a single cortical column encode passive sensory information using large, heterogeneous receptive fields covering the digits and palm (Tutunculer et al, 2006), and the timing between spikes contributes to a distributed spatiotemporal code . In the awake animal, recorded neuronal activity can be used to encode the placement of footfalls on a treadmill with a sensitivity of Ͼ90%.…”
Section: Injury-related Changes In Tactile Representation Within S1mentioning
confidence: 99%